Model Peta Konsep pada Pembelajaran Pendidikan Agama Islam di Politeknik Kesehatan Mataram - Lenny Herlina (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
Islamic Religious Education at higher education institutions is a Compulsory Curriculum Subject family, generally taken in the first semester of 2 credits or the equivalent of 14 meetings with a duration of 90 to 120 minutes of meeting. The number of meetings and the time required requires a lecturer in Islamic Religious Education to be able to convey learning effectively and efficiently and with a formula that makes it easier for students to absorb and understand learning material more quickly. Descriptive qualitative research through interviews and observations to obtain primary data and documentation to obtain secondary data aims to obtain in-depth information regarding the model applied to learning Islamic Religious Education at the Mataram Health Polytechnic. The results of the study show that the lecturers for the Islamic Religious Education Course choose to use the Concept Map Model in facilitating students to achieve the learning objectives that have been set.